Conspiracy, apocalypticism, and contingency in Smith Henderson's Fourth of July Creek. Issue 4 (1st October 2016) - Titlestad, Michael Frank
Abstract: This essay presents a narrative analysis of Smith Henderson's debut novel, Fourth of July Creek (2014). Woven into an account of its plot and concerns is a description of contending epistemologies: the first (which is heuristic and contingent) is manifest in the life of Pete Snow, a social worker in Montana, the second (adamant in its teleological convictions) is the doctrine of a right-wing conspiracist, Jeremiah Pearl. A more general account of conspiracism and apocalypticism then examines the ways in which survivalism exists at the confluence of the two. Although various scholars have defended conspiracy theories, there are clear reasons why Pearl's world view is spectacularly harmful. In Pete Snow's practice, the novel presents a contrary approach to meaning, which can be characterized as consonant with philosophical pragmatism. At its conclusion, the argument endorses Snow's uncertain and muddled progress through the world, which it interprets as a persuasive and productive counter to life in a prison house of fatalistic ideology.